(untitled) (Scientia Agricola, 2001)
Four genotypes of papaya (Carica papaya L.) two from the 'Solo' group (Sunrise Solo and Improved Sunrise Solo line 72/12) and two from the 'Formosa' group (Tainung 02 and Known-You 01), grown in Macaé, RJ, Brazil (lat. 22(0) 24' S, long. 41(0) 42' W), were used in this study. Twenty-five mature leaves from each genotype were sampled four and five months after seedling transplant to the field to determine the length of the leaf central vein (LLCV) and the leaf area (LA). According to covariance analyses there were no significant differences in the slope and intercept of the mathematical models calculated for each genotype. Thus, a single mathematical model (Log LA = 0.315 + 1.85 Log LLCV, R²=0.898) was adjusted to estimate the LA using the length of LLCV for the four genotypes. An unique model can be applied to estimate the LA for the four papaya genotypes using LLCV in the range from 0.25 to 0.60 m, and for papaya trees 150 to 180 days after transplanting.